A visão de um estudante sobre o processo avaliativo de um curso de medicina baseado em metodologias ativas de ensino e aprendizagem, em uma universidade federal no interior do estado de São Paulo, entre os anos de 2019 e 2024 - Bispo, João Paulo Borges (Universidade Federal de São Carlos, 2024)
The evolution of medical education reflects the pressing need to adapt to the complexities of modern society, which demands that future physicians develop not only robust knowledge but also essential skills and attitudes. Traditionally, assessments have prioritized categorization, focusing primarily on measuring the adequacy of outcomes. However, contemporary approaches advocate for the adoption of active learning methodologies and integrated evaluation processes, aiming to create a more holistic educational experience. This study seeks to examine the alignment between the assessment practices of the medical program at the Federal University of São Carlos (UFSCar), contemporary standards in medical education, and their impact on academic training after 19 years of the program's implementation. Particular emphasis is placed on the students’ critical and reflective experiences, offering insights into how these practices shape their educational journey. This study adopts a basic research design with a qualitative approach, combining bibliographic and documentary analysis with a critical-reflective narrative to conduct an exploratory examination of the subject. The research involved a literature review on assessment processes in medical education, an analysis of the political-pedagogical project of UFSCar's medical program, and an in-depth examination of the critical-reflective portfolio of a medical student at UFSCar between 2019 and 2024. Student assessment is a cornerstone of medical education, serving not only to evaluate academic performance but also to cultivate the essential competencies required for professional practice. The evolution of educational paradigms has introduced approaches that prioritize continuous learning, integrating the evaluation of knowledge, skills, and attitudes. Effective assessment must balance formative, summative, and informative functions: tracking learning progress, guiding student development, and evaluating the quality of educational delivery. In this context, programmatic assessment emerges as an innovative and integrative approach, leveraging a variety of evaluation methods to offer a holistic and longitudinal view of student learning. This discussion explores the author’s experiences within the medical program at UFSCar, which introduced an innovative curriculum centered on competency-based education and programmatic assessment. Initially, the shift from a traditional, outcome-focused model to one emphasizing active learning and continuous assessment proved challenging. Adapting to active methodologies and programmatic evaluations required significant effort, reflecting the inherent complexities of such a transition. The author observed an initial alignment with the program's pedagogical goals; however, inconsistencies. This divergence highlighted the need for greater cohesion in implementing innovative practices. Despite the evident benefits of the system, the author identified areas for improvement. Participation in the Evaluation Committee (NAv) was particularly impactful, offering a transformative experience that enhanced understanding of the assessment framework and enabled active contributions to its refinement. In conclusion, while the program lays a robust foundation for medical education, there remains significant potential for refinement. In the UFSCar medical program, the curriculum is structured around competencies and active methodologies, adopting a constructivist approach with continuous assessment. While this framework aligns with contemporary assessment guidelines in theory, practical challenges remain. These include the need for a clearer understanding of assessment processes, as well as greater diversity and transparency in the criteria and tools employed. Programmatic assessment emerges as a promising solution. This approach has the potential to make learning more meaningful and impactful. However, achieving a true transformation of assessment systems requires a cultural shift in the teaching process. True renewal of assessment systems requires cultural change and continuous education among all education stakeholders. Thus, assessment can effectively become a moment of learning and for learning.
The assessment based on active teaching and learning methodologies in a medical school at a federal university located in São Paulo state under a student's perspective 2019-2024
Keywords: Educação médica; Sistema de avaliação; Estudante de medicina; Narrativa crítico-reflexiva; Medical education; Evaluation system; Medical student; Critical-reflective narrative; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL